Development and results of the epilepsy surgery in Armenia: hope for a better future - Sukhudyan, Biayna; Minkin, Krasimir; Badalyan, Sevak; Gabrovski, Kaloyan; Gevorgyan, Ani; Tovmasyan, Irina; Babloyan, Ara; Dimova, Petia (Frontiers in Neurology, 2023)
Purpose We present our experience with the national epilepsy surgery program in Armenia by tracing the development of epilepsy surgery in the largest pediatric neurology department at “Arabkir” Medical Center. This development was possible on the basis of a strong collaboration with the Epilepsy Surgery center at the University Hospital “Sofia St. Ivan Rilski,” Sofia, Bulgaria. Materials and methods Our material included 28 consecutive patients with lesional drug-resistant epilepsy evaluated. All patients underwent 3 T MRI and Video-EEG monitoring. Brain 18FDG-PET was done in 13 patients in St. Petersburg. Fifteen patients (53%) had preoperative neuropsychological examination before surgery. All operations were done by the same neurosurgical team on site in Arabkir Hospital. Results The majority of the patients in our cohort benefited from the epilepsy surgery as 25 (89%) are free of disabling seizures (Engel class I) and three patients (11%) did not improve substantially (Engel class IV). Eleven patients (39%) are already ASM-free after surgery, 4 (14%) are on monotherapy, 11(39%) get two drugs, and 2(7%) are on polytherapy, one of them still continues having seizures. In 12 patients (43%), we were able either to withdraw therapy or to decrease one of the ASM. Conclusion We believe that, although small, yet encompassing patients along the usual age spectrum and with the most frequent pathologies of drug-resistant epilepsies, our experience can serve as a model to develop epilepsy surgery in countries with limited resources.